0670 The Outcome Of Cpap Titration Under Drug-induced Sleep Endoscopy: A Randomized Controlled Crossover Trial. (27th May 2020) - Wang, T; Lin, T; Ni, Y; Lo, Y
Abstract: Introduction: The titration pressure of continuous positive airway pressure (CPAP) is an important issue for patients with obstructive sleep apnea (OSA). The aim of this study was to understand the impact of drug-induced sleep endoscopy (DISE)-guided CPAP pressure and doctor-guided CPAP pressure on patients with OSA. Methods: In this randomized controlled single-blinded crossover trial, we compared the effects of 1 month CPAP treatment on patients with OSA. Twenty-four patients with OSA were recruited and completed this study. They all underwent polysomnography, DISE-guided CPAP titration and accommodation. Doctor-guided CPAP pressure was determined before DISE. Patients were randomly assigned to receive DISE-guided or Doctor-guided CPAP pressure treatment for 1 month. Then, they switched to another CPAP pressure for another 1 month. Epworth sleepiness scale (ESS) will be recorded at baseline, 1 month and 2 months. Results: The DISE-guided CPAP pressure and Doctor-guided CPAP pressure had no significant difference (13.9±0.7 cm H2 O vs 13.5±0.5 cm H2 O; P=0.92). In addition, residual AHI and compliance were also no significant difference between two groups. The ESS was significantly improved from baseline to 1 month CPAP treatment in both groups. Epiglottis (anterior-posterior collapse) was significant associated with AHI (P < 0.001, by Spearman correlation). Both Epiglottis (anterior-posterior collapse) and tongue base collapse were significant associated with 95% CPAP pressure (P = 0.031 and 0.038). After multivariate regression analyses, epiglottis (anterior-posterior collapse) is the independent factor for 95% CPAP pressure. Conclusion: The DISE-guided CPAP pressure and Doctor-guided CPAP pressure had no significant difference on the improvement of ESS. Epiglottis (anterior-posterior collapse) is the independent factor for AHI and 95% CPAP pressure. Support: Chang Gung Memorial Hospital and Chang Gung University